KUALITAS PELAPORAN KEUANGAN SKPK, PENERAPAN STANDAR AKUNTANSI PEMERINTAH BERBASIS AKRUAL, KEBIJAKAN AKUNTANSI DAN PENGENDALIAN INTERNAL DI SATUAN KERJA PERANGKAT ACEH - Ramadhana, Andriansyah; Saputra, Mulia; Fachruddin, Rudy (Jurnal Ilmiah Mahasiswa Ekonomi Akuntansi, 2023)
This study aims to examine the influence of the application of accrual-based government accounting standards, accounting policies, and internal controls on the quality of financial reporting in the Aceh Work Unit. The population of this research is all SKPA in the Government of Aceh, totaling 48 SKPA with a sample of 96 people. The data analysis method in this study is multiple regression analysis processed using the SPSS (Statistical Package for Social Science) program based on the answers from the respondents. The results showed that the application of accrual-based government accounting standards, accounting policies, and internal control partially and simultaneously affected the quality of reports and financial statements.